Antitumoral activity of liraglutide, a new DNMT inhibitor in breast cancer cells in vitro and in vivo - Chequin, Andressa; Costa, Luiz E.; de Campos, Felipe F.; Moncada, Angie D.B.; de Lima, Lucas T.F.; Sledz, Lucas R.; Picheth, Guilherme F.; Adami, Eliana R.; Acco, Alexandra; Gonçalves, Marcos B.; Manica, Graciele C.M.; Valdameri, Gláucio; et al. (Chemico-biological interactions, 2021)
Breast cancer (BC) is the most frequently diagnosed female cancer and second leading cause of death. Despite the discovery of many antineoplastic drugs for BC, the current therapy is not totally efficient. In this study, we investigated the potential of repurposing the well-known diabetes type II drug liraglutide to modulate epigenetic modifications in BC cells lines in vitro and in vivo via Ehrlich mice tumors models. The in vitro results revealed a significant reduction on cell viability, migration, DNMT activity and displayed lower levels of global DNA methylation in BC cell lines after liraglutide treatment. The interaction between liraglutide and the DNMT enzymes resulted in a decrease profile of DNA methylation for the CDH1, ESR1 and ADAM33 gene promoter regions and, consequently, increased their gene and protein expression levels. To elucidate the possible interaction between liraglutide and the DNMT1 protein, we performed an in silico study that indicates liraglutide binding in the catalytic cleft via hydrogen bonds and salt bridges with the interdomain contacts and disturbs the overall enzyme conformation. The in vivo study was also able to reveal that liraglutide and the combined treatment of liraglutide and paclitaxel or methotrexate were effective in reducing tumor growth. Moreover, the modulation of CDH1 and ADAM33 mouse gene expression by DNA demethylation suggests a role for liraglutide in DNMT activity in vivo. Altogether, these results indicate that liraglutide may be further analysed as a new adjuvant treatment for BC. •Liraglutide an inhibitor of proliferation and migration of breast cancer cell lines.•Liraglutide promotes global demethylation by DNMT inhibition.•Liraglutide as a new DNMT inhibitor suitable to breast cancer adjuvant therapy.